Karakteristik Body Scrub Pada Variasi Perbandingan Ekstrak Kulit Buah Kakao dan Ekstrak Kulit Lemon Serta Waktu Pengadukan - Machtum, Rahiqi; Putra, Gusti Putu Ganda; Wrasiati, Luh Putu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
A body scrub is a treatment that coats the entire surface of the body's skin. The composition of raw materials and stirring time in the body scrub manufacturing process will affect the characteristics of the product. This ponder points to decide the impact of the proportion of cocoa natural product peel extricate and lemon peel extricate and mixing time on the characteristics of the bodyscrub and decide the proportion of cocoa natural product peel extricate: lemon peel extricate and certain mixing time to deliver the leading body clean. The experimental design utilized in this consider could be a two-factor factorial RBD (Randomized Block Design) gathered by time of fabricate. The primary calculate is the proportion of additional cocoa natural product peel and lemon extricate with a proportion of 3 levels, to be specific (1:1), (2:1), (3:1). The moment calculate is blending time which comprises of 3 levels, to be specific 15, 20, and 25 minutes. Information were analyzed by investigation of fluctuation and proceeded with Duncan's test. The factors watched in this consider were dampness substance, pH, viscosity, spreadability, separation ratio, antioxidant activity, and organoleptics. The comes about appeared that the proportion of cocoa case extricate and lemon extricate and mixing time had an awfully critical impact on moisture content, spreadability, viscosity, aroma organoleptic, color organoleptic, and texture organoleptic. The interaction had a really critical impact on antioxidant action. From the effectiveness index test, it was obtained that the treatment of the ratio of cocoa pod extract and lemon extract (1:1) and mixing time of 15 minutes was the leading treatment to deliver a body clean with the characteristics of the water substance esteem of 33.73%, pH 7, viscosity 27,950 cp, spreadability 6.28 cm, separation ratio = 1, antioxidant activity 118. 28 mg/ml, organoleptic aroma 5.75 (mildly liked-liked),